Upaya Hukum Filipina untuk Mendapatkan Hak Berdaulat atas Kepulauan Kalayaan (Kepulauan Spartly) - Olivia Lebrina Inuhan; Lucia Charlota Octovina Tahamata; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The Spratly Archipelago are one of the archipelago located in the South China Sea and have relatively many natural potentials so that these islands are claimed by several countries, one of which is the Philippines. The Philippines claims several islands and considers that the Philippines has legality of sovereign rights in the Philippine Exclusive Economic Zone, and names the claimed islands as the Kalayaan islands, but the claims made by the Philippines are challenged by several countries, one of which is China. Therefore, this paper will further examine Philippine legal efforts to gain sovereign righs over the Kalayaan acrhipelago (Spratly Archipelago).Purposes of the Research: The purpose of this writing is, the legality of the Philippine sovereign rights in the Kalayaan Archipelago (Spartly Archipelago) according to UNCLOS 1982.Methods of the Research: Research methods are used with namely normative research types, statutory approaches and case approaches, primary legal materials and secondary and material collection procedures using library research and documentary studies.Results of the Research: From the results of the research, the problem shows that the legality of the Philippines, which is a coastal state, has sovereign rights over the EEZ in its territory. The claim made by the Philippines in the Spratly Islands against Kalayaan can be said to be legal because it has a fairly strong juridical and factual basis, seen when the Arbitase Court in The Hague won the Philippine lawsuit over the case of the Spratly Islands which has been claimed as its territory. The judge emphasized that China does not have an Exclusive Economic Zone in the Spratly Islands, which has been in dispute with the Philippines. Each coastal State is obliged to respect each other's sovereign rights in the EEZ of each country. The Philippines must take a new way to gain legal force on the sovereign rights of the Philippine EEZ, one of which is to submit a request to the International Court of Justice to cooperate and make a joint agreement with the disputing countries so that the legality of the Philippines' sovereign rights is recognized.